Prognostic value of coronary revascularisation-related myocardial injury: a cardiac magnetic resonance imaging study. - Rahimi, K; Banning, A; Cheng, A; Pegg, T; Karamitsos, T; Channon, K; Darby, S; Taggart, D; Neubauer, S; Selvanayagam, J (2009)
AIMS: Myocardial revascularisation improves outcomes in patients with coronary artery disease. However, these procedures may themselves cause irreversible myocardial injury. The prognostic value of procedural myocardial injury is uncertain. METHODS AND RESULTS: We quantified procedural myocardial necrosis using delayed enhancement cardiovascular magnetic resonance imaging (DE-CMR) in 152 consecutive patients before and shortly after percutaneous coronary intervention (PCI) or coronary artery bypass graft (CABG). The primary endpoint was defined as death, non-fatal myocardial infarction, sustained ventricular arrhythmia, unstable angina or heart failure requiring hospitalisation. During a median follow-up of 2.9 years, 27 patients (18%) reached the primary endpoint. 49 patients (32%) had evidence of new procedure-related myocardial hyperenhancement with a median mass of 5.0 g (interquartile range 2.7-9.8). After adjustment for age and sex, these patients had a 3.1-fold (95% confidence interval 1.4 to 6.8; p = 0.004) higher risk of adverse outcome than patients without new hyperenhancement. Cardiac troponin levels and quantitative measures of left ventricular function after procedure did not show any significant independent association with the primary endpoint and they did not alter the independent association of new hyperenhancement. CONCLUSIONS: Myocardial injury during PCI or CABG, identified by DE-CMR, adversely affects clinical outcome. This suggests the benefits from revascularisation could partially be offset by new myocardial injury caused by the intervention itself.